TINJAUAN HUKUM TERHADAP KONTRAKTOR PENAMBANG BATU BARA DAN KONTRAKTOR REKLAMASI DALAM PELAKSAAN REKLAMASI LAHAN PASCA TAMBANG DI KOTA SAMARINDA - Achmad Chairil Ardi Baruna (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTAgreements between the holders of coal mines with contractors, the parties who make agreements have equal positions in the fight for their rights and obligations, so as to be balanced rights and obligations between them. The contents of the agreement between the holders of the mine with the contractor contain the scope of post-mining land reclamation work in the mining area. In its agreement, the time period has been agreed upon. The problem of the thesis is how to perform the reclamation agreement between the holders of mines and contractors, post-mining and how to sanction to the mining business license holders and contractors if not running Reclamation in accordance with the agreed agreement, with the title of the thesis. The research of this thesis is normative and juridical juridic empirical, the nature of his research is a descriptive analysis of the direct view of the Treaty and application of reclamation between the holders of the mines and contractors in Samarinda. The results of the study explain the agreement between the holders of coal mines with the contractor has fulfilled the legal requirements of the agreement as in article 1320 Civil Code, that is to agree on those who bind themselves that the agreement has occurred and Approved by both parties, capable to make agreements, and with an agreement in the implementation of post-mining land reclamation in Samarinda. The sanctions of mine and contractor permits in the event of violations of reclamation and postwar activities may be subject to administrative sanctions and criminal sanctions. Keywords: Reclamation and Sanctions